Problems of Modern Russian Language and Methods of its Installation or New Suggestions for Enhancing Student Knowledge Through Interactive Methods - Osmanova Maryam Soibkhonovna (Genius Journals, 2022)
The article discusses the need to develop students' literacy in oral and written texts in the state language, to create meaning in our language - to feel the primary feature, to understand that the future is the basis of a noble word in the development of all spheres of society. Teachers will also be given some tips to strengthen students' spelling skills.
Keywords: listening and comprehension; sound changes; capitalization; hyphenation